The influence of strategic HRM and sector on perceived performance in health services organizations - Rodwell, J.; Teo, Stephen (Routledge, 2008)
In this study, we examine a variety of management characteristics of for-profit and not-for-profit organizations in the health services (HS) industry. Data collected from Australian senior executives are used to test the relationships between managerial constructs such as employee commitment, customer demandingness, strategic HRM orientation and the adoption of human capital-enhancing human resource (HR) practices and perceived overall performance. Data analysis conducted using the Partial Least Square Modeling show a statistically significant path from commitment to employees, customer demandingness and strategic HRM orientation to the adoption of human capital-enhancing HR practices (such as selective staffing, comprehensive training, and performance appraisal) to perceived organizational performance. The results also show that private sector health service organizations have a higher level of perceived performance.